3a x 2b is 6ab
lets break it up
(3a) = 3 x a
(2b) = 2 x b
therefore: 3a x 2b = 3 x a x 2 x b
lets times the numbers first
3 x 2 = 6
now the letters
a x b = ab
remember it does not matter what order you put the letters ab = ba
abx 6 = 6ba
if two like terms times each other it will be similar except for the pronumeral part i will now give an example below:
4a x 4a
lets break it up
(4a) = 4 x a
(4a) = 4 x a
therefore: 4a x 4a = 4 x 4 x a x a
4 x 4 = 16
a x a = a
therefore
a x 16 = 16a
now for the problem:
Remember to still use BODMAS or BIDMAS
what is 7a x (b x (6 x 3)) x 2a = ?
to report any problems with this problem go here
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
7 a × ( b × ( 6 × 3 ) ) × 2 a = 7 a × 1 8 b × 2 a = 2 5 2 a 2 b